2002
DOI: 10.1007/s101200200000
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer treatment guidelines in Japan

Abstract: Recent developments in treatment modalities for gastric cancer have allowed the selection of a variety of treatments, and this has resulted in some confusion in daily practice. The Japan Gastric Cancer Association issued the first edition of Gastric cancer treatment guidelines in March, 2001 to provide a common basis of understanding of the extent of disease and selection of proper treatment among doctors, patients, and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
341
1
12

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(355 citation statements)
references
References 22 publications
0
341
1
12
Order By: Relevance
“…Curative resection for gastric cancer essentially requires an adequate extent of lymphadenectomy as well as gastric resection to improve therapeutic outcomes [6][7][8]. The general surgical community has concerns about limited lymphadenectomy for laparoscopic procedures, although several prospective clinical trials have demonstrated LADG to be superior to an open procedure because it results in less postoperative pain, faster recovery and better cosmetic results [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curative resection for gastric cancer essentially requires an adequate extent of lymphadenectomy as well as gastric resection to improve therapeutic outcomes [6][7][8]. The general surgical community has concerns about limited lymphadenectomy for laparoscopic procedures, although several prospective clinical trials have demonstrated LADG to be superior to an open procedure because it results in less postoperative pain, faster recovery and better cosmetic results [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…The general surgical community has concerns about limited lymphadenectomy for laparoscopic procedures, although several prospective clinical trials have demonstrated LADG to be superior to an open procedure because it results in less postoperative pain, faster recovery and better cosmetic results [2,3]. For distal AGC, the Japanese Gastric Cancer Association has presented complete D2 lymphadenectomy including lymph nodes numbers 11p, 12a, and 14v as the standard therapy and LADG observing this guideline necessitates a lot of experience, skill, efforts and times [6,8]. As a result, most surgeons only perform LADG for cases of EGCs, in which the rate of lymph node metastasis is not as high as in AGC and limited lymphadectomy is enough to oncological demands.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol was approved by the JCOG Protocol Review Committee and the institutional review boards (IRBs) of each of the 17 participating Japanese hospitals before the activation of the study. The inclusion criteria were as follows: histologically confi rmed adenocarcinoma of the stomach, a c-stage IA (T1N0) or IB (T1N1/T2N0) tumor according to the Japanese classifi cation of gastric carcinoma, 2nd English edition [17], no indications for endoscopic mucosal resection (EMR) according to the Japanese endoscopic treatment guidelines [2] ("no indications for EMR" corresponds to a clinical node-positive or clinical nodenegative status with any of the following criteria: a tumor size 2 cm or larger, invasion to the submucosa or deeper, a histologically undifferentiated type, the presence of an ulcer or ulcerative scar [in the case of depressed type], or the impossibility of an en-bloc resection), a distal gastrectomy-treatable tumor located in the middle or lower third of the stomach, no involvement of the duodenum, a patient age of 20-80 years, an Eastern Cooperative Oncology Group (ECOG) performance status (PS) of 0 or 1, a body mass index (BMI) of less than 30 kg/m 2 , the absence of a recurrent tumor after EMR, no prior upper abdominal surgery or intestinal resection other than an appendectomy, no prior chemotherapy or radiotherapy for any malignancy, adequate organ function, and written informed consent. The exclusion criteria were as follows: a synchronous or metachronous (within 5 years) malignancy other than carcinoma in situ or mucosal cancer, pregnancy or lactation, severe mental disease, the systemic administration of corticosteroids, unstable angina or myocardial infarction within 6 months before registration, uncontrolled hypertension, diabetes mellitus (both uncontrolled and controlled with insulin), and severe respiratory disease requiring continuous oxygen therapy.…”
Section: Methodsmentioning
confidence: 99%
“…The Japanese guidelines allow laparoscopy-assisted gastrectomy as an investigational treatment for early gastric cancer, with consideration of the patient's performance status [2]. Since Kitano et al [3] reported the fi rst laparoscopyassisted gastrectomy in 1994, this technique has attracted the attention of surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…Informed consent was obtained from all patients. Specimens were evaluated according to the Japanese Classification of Gastric Carcinoma established by the Japanese Research Society for Gastric Cancer [5]. Patients who had a surgical risk greater than American Society of Anesthesiology (ASA) III, a previous history of upper abdominal surgery (excluding cholecystectomy, etc.)…”
Section: Methodsmentioning
confidence: 99%